THE INFLUENCE OF PRICE, CO-BRANDING, AND VIRAL MARKETING ON THE PURCHASE DECISION FOR HMNS X TSANA RINTIK SEDU PERFUME - Widya Adesti Sriningsih; Lia Julaeha (International Journal Management and Economic, 2026)
This research aims to analyze the effect of price, co-branding, and viral marketing on the purchase decision of HMNS x Tsana Rintik Sedu perfume. The analysis method in this research uses quantitative primary data with data collection techniques through questionnaires to 100 respondents. Data analysis techniques use multiple linear regression with the help of SPSS. The results of the research show that the variables of price and viral marketing have a partial and significant effect, while the variables of co-branding does not have a partial and significant effect on the purchase decision of HMNS x Tsana Rintik Sedu perfume. In addition, price, co-branding, and viral marketing have a simultaneous effect on the purchase decision of HMNS x Tsana Rintik Sedu perfume.